The role of Staphylococcus aureus in allergic disease and cross-reactivity in fish allergy - Sørensen, Martin (UiT The Arctic University of Norway, 2017)
Aims: The aims was to describe prevalence`s of allergic disease in adolescents and study associations between allergic diseases and Staphylococcus aureus. Secondly, to study cross-reactivity in fish allergic children and the utility of existing and novel tests for fish allergy. Material and Methods: Prevalence of allergic diseases and associations to Staphylococcus aureus was studied in a cross-sectional study including 868 adolescents using a questionnaire and clinical examinations/laboratory tests. Cross-reactivity in fish allergy was studied with food challenges with different fish species, questionnaire and measurement of specific IgE in 35 fish allergic children. Results: Prevalence of asthma, atopic dermatitis and allergic rhinitis was 11.9%, 10.4% and 26.0%, respectively. 10% had more than one allergic disease and the lifetime prevalence for any allergic disease was 45.1 %. 40% were sensitized to at least one allergen. S.aureus carriage was associated with the severity of allergic disease whereas sensitization to staphylococcal enterotoxins was associated with allergic multimorbidity and poly-sensitization to food and inhalant allergens. Partial tolerance was found in one third of fish allergic children regarding any allergic symptoms and in more than half regarding only objective allergic symptoms. IgE to cod extract >8.2 kUA/L or salmon extract >5.0 kUA/L discriminated best between non-tolerance and partial tolerance. Sensitization to enolase or aldolase were found only in patients with objective allergic symptoms, but were negative in many patients with allergy. Conclusions: Staphylococcus aureus carriage may play a role in disease severity, whereas sensitization to staphylococcal enterotoxins may play a role in poly-sensitization to food- and inhalant allergens and allergic multimorbidity. Cross-reactivity among fish allergic patients is common, but tolerance to some species exist in around one third and should be identified to avoid unnecessary food restrictions. A combination of clinical ...